Recommendations for the emergency management of complications associated with the new direct oral anticoagulants (DOACs), apixaban, dabigatran and rivaroxaban - Steiner, Thorsten; Böhm, M.; Dichgans, M.; Diener, H.-C.; Ell, C.; Endres, M.; Epple, C.; Grond, M.; Laufs, U.; Nickenig, G.; Riess, H.; Röther, J.; et al. (Clinical research in cardiology, 2013)
Dabigatran, apixaban, and rivaroxaban have been approved for primary and secondary stroke prevention in patients with atrial fibrillation. However, questions have arisen about how to manage emergency situations, such as when thrombolysis would be required for acute ischemic stroke or for the managing intracranial or gastrointestinal bleedings. We summarize the current literature and provide recommendations for the management of these situations. Peak plasma levels of the direct oral anticoagulants (DOACs) apixaban, dabigatran, or rivaroxaban are observed about 2-4 h after intake. Elimination of dabigatran is mainly dependent on renal function. Consequently, if renal function is impaired, there is a risk of drug accumulation that is highest for dabigatran followed by rivaroxaban and then apixaban and thus dosing recommendations are different. To date, no bedside tests are available that reliably assess the anticoagulatory effect of DOACs, nor are specific antidotes available. We recommend performing the following tests if DOAC intake is unknown: dabigatran-associated bleeding risk is minimized or can be neglected if thrombin time, Hemoclot test, or Ecarin clotting time is normal. Apixaban and rivaroxaban effects can be ruled out if findings from the anti-factor Xa activity test are normal. High plasma levels of DOAC are also mostly excluded if PTT and PTZ are normal four or more hours after DOAC intake. However, normal values of global coagulation tests are not sufficient if thrombolysis is indicated for treating acute stroke. The decision for or against thrombolysis is an individual decision; in these cases, thrombolysis use is off-label. In case of bleeding, prothrombin complex concentrates seems to be the most plausible treatment. For severe gastrointestinal bleeding with life-threatening blood loss, the bleeding source needs to be identified and treated by invasive measures. Use of procoagulant drugs (antifibrinolytics) might also be considered. However, there is very limited clinical experience with these products in conjunction with DOAC.
Published online: 14 May 2013
Gesehen am 18.02.2022